THE CORRELATION BETWEEN HUMAN RIGHTS AND HUMAN OBLIGATIONS (AN ANALYSIS OF ISLAMIC CRIMINAL LAW) - Hasan, Hamzah; Ahmad, La Ode Ismail (Jurnal Diskursus Islam, 2020)
This article will try to see how the correlation between Human Rights Obligations and Human Rights when viewed in the perspective of Islamic Criminal Law. The theme of Human Rights Obligations, by scientists and the world community, is not an issue that is considered as important as the issue of Human Rights. Even though the Human Rights Obligation is an important point of whether human rights are upright or not. The description of the relationship is in the concept of Islamic criminal law as summarized in al-Daruriyyat al-khamzah (religious preservation obligations, life obligations, obligations to preserve reason, obligations to preserve offspring and obligations to preserve property.